STYK1/NOK affects cell cycle late mitosis and directly interacts with anaphase-promoting complex activator CDH1. Issue 12 (December 2022) - Zeng, Su-Lin; Patel, Suraj S.; Lv, Mo-Qi; Zhu, Daphne; Shen, Wen H.; Liu, Li
Abstract: The novel oncogene STYK1/NOK plays critical roles in cancer development. However, its regulation during cell division is less defined. In this paper, we show that over-expression of STYK1/NOK caused mitotic arrest and cytokinesis defects. The protein level of STYK/NOK fluctuated during the cell cycle, with a peak at mitosis and a quick reduction upon mitotic exit. The cell cycle-related expression pattern of STYK1/NOK resembled the one of aurora kinases and polo-like kinase 1. Depletion of APC3 led to accumulation of STYK1/NOK and to the G2/M arrest. Co-immunoprecipitation experiment demonstrated the direct interaction of STYK1/NOK with CDH1. Overexpression of CDH1 shortened the half-life of STYK1/NOK. The kinase domain, but not the five D boxes, of STYK1/NOK was responsible for the interaction with CDH1. Altogether, our data demonstrated for the first time that STYK1/NOK could affect cell division, probably by directly targeting key components of APC/C such as CDH1 at late mitosis. Current study may provide a vital mechanistic clue for understanding the roles of STYK1/NOK in mitosis and cytokinesis during STYK1NOK mediated genomic instability and oncogenesis. Abstract : Cell cycle; STYK1/NOK; APC/C; Protein-protein interaction; CDH1.